Defining the core group of the genus Gomphonema Ehrenberg with molecular and morphological methods. Issue 1 (2nd January 2020) - Abarca, Nélida; Zimmermann, Jonas; Kusber, Wolf-Henning; Mora, Demetrio; Van, Anh T.; Skibbe, Oliver; Jahn, Regine
ABSTRACT: In order to understand the taxonomy and phylogeny of the genus Gomphonema, the type of the name of the genus, G. acuminatum, and related species complexes are studied with an integrative taxonomic approach. Sixty-seven unialgal Gomphonema strains were established from 34 different water bodies in Croatia, Faroe Islands, Finland, Iceland, Germany, Mexico, Spain, Switzerland and Korea, which provided molecular (18S and rbc L), morphometric and ultrastructural data. Our study was complemented by molecular data from INSDC, summing up the studied data to 82 freshwater Gomphonema strains from the G. acuminatum and related species complexes which are here defined as the Gomphonema core group. Except for outline variations which occur even within one clone, their micro-morphologies are indistinguishable. The molecular data of the two markers clustered the taxa of the core group into one clade, well differentiated from other Gomphonema taxa such as G. augur and G. parvulum . For differentiation within the clade, the plastid marker rbc L provided better species resolution comparable to traditionally recognized taxa. The combined analysis of the molecular as well as morphological data resulted in the defining of only 7 subclades in contrast to 20 currently assigned names for the taxa of the Gomphonema core group in this study. The Gomphonema core group has been overdescribed due to the use of outline as the main criterion for species delimitation. A polyphasic approach, combining molecular and micromorphological data for taxonomy, nomenclatural evaluation, and observations from clonal cultures can reveal the full intricacies of evolutionary relations.